Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1097/00005373-199502000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Coronal Fracture of the Body of the Hamate

Abstract: Fractures of the body of the hamate are unusual. Eleven patients with coronal fractures of the hamate bone, all involving dislocation of the hamate-metacarpal joint, are reported. Routine roentgenograms were not helpful in delineating the presence of the injury in five patients; therefore, fracture diagnosis was not initially made in those patients. The average delay in diagnosis of this group was 10 days. A 30-degree pronated view, tomograms, and computed tomography scans may be necessary in the diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
49
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 9 publications
3
49
0
Order By: Relevance
“…2 Computerised axial tomography is a useful adjunct in the diagnosis of these injuries. [4][5][6][7]9 Early investigation with three dimensional computed tomography (3D-CT) has been advocated. 7 In this particular case, multiple axial views provided adequate definition of the fracture lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Computerised axial tomography is a useful adjunct in the diagnosis of these injuries. [4][5][6][7]9 Early investigation with three dimensional computed tomography (3D-CT) has been advocated. 7 In this particular case, multiple axial views provided adequate definition of the fracture lines.…”
Section: Discussionmentioning
confidence: 99%
“…3 Due to the mechanism of injury, an associated carpometacarpal dislocation involving the fourth and fifth metacarpal bases may be present. [3][4][5]7 This fracture pattern is inherently unstable because of the action of the long flexor and extensor tendons. Early diagnosis is essential to minimize the risk of painful arthritis, muscle imbalance and potential loss of grip strength.…”
mentioning
confidence: 99%
“…A prior case was treated successfully with open reduction and K-wire fixation of both the hamate and capitate. 2 In the limited number of published case series of coronal hamate fractures most investigators have observed good results with open reduction and internal fixation using either K-wires, 2-5 lag screws, 6 or a Herbert screw. 7 One attempt at closed treatment resulted in residual fourth and fifth metacarpal dorsal subluxation after the patient was noncompliant with splinting.…”
Section: Discussionmentioning
confidence: 99%
“…1 A fracture in the coronal plane of the capitate has been described and was associated with a coronal hamate fracture. 2 We present a case of a fracture of the capitate in the coronal plane in conjunction with a fracture of the hamate in the coronal plane treated satisfactorily with open reduction and internal fixation of the hamate only. The diagnosis was delayed because of the rarity of the injury.…”
mentioning
confidence: 99%
“…As such, diagnosis has been delayed as long as three months postinjury in some cases (4). It has been suggested that when a boxer's fracture is not found after a significant punching injury, fracture of the hamate should be suspected (3). Pain at the ulnar side of the hand in the absence of routine radiological findings, as well as fractures of the fourth metacarpal base, should warrant an oblique x-ray.…”
Section: Discussionmentioning
confidence: 99%